Sunteți pe pagina 1din 27

Question# 5 For Matrices A = following rules: (i) Solution L.H.

S = A + C = + A+C=C+A ,B= and C = , verify the

= R.H.S = C + A = +

= Hence, A+C=C+A (ii) A +B = B + A


Page 1

Mudassar Nazar Notes

Solution L.H.S = +

L.H.S =

= Hence, A+B = B+A

(iii) Solution

B+C=C+B

L.H.S = B + C = +

Mudassar Nazar Notes

Page 2

= R.H.S = C + B = +

= Hence, B+C=C+B

( iv) Solution

A + ( B + A) = 2A + B L.H.S = A + ( B + A) = +

Mudassar Nazar Notes

Page 3

= R.H.S = 2A + B =2 +

= Hence, A + ( B + A) = 2A + B

(v)

(C - B) +A = C +(A - B)

Solution
L.H.S = +

Mudassar Nazar Notes

Page 4

= R.H.S = C + (A B ) = +

= Hence, (C B) +A = C + (A B )

(vi)

2A +B = A + ( A +B) L.H.S = 2A + B =2 +

Solution

Mudassar Nazar Notes

Page 5

= R.H.S = A + (A + B) = +

= Hence, 2A + B = A + ( A+ B)

(vii) Solution

(C B ) A = (C A ) B
L.H.S. = (C B ) A = ( C A ) B = -

Mudassar Nazar Notes

Page 6

= R.H.S = ( C A ) - B = -

= Hence, (CB)A=(CA)B

(viii) Solution

( A + B ) + C = A + ( B + C)
L.H.S = ( A + B ) + C = +
Page 7

Mudassar Nazar Notes

= R.H.S = A + ( B + C ) = +

= Hence, ( A + B ) + C = A + ( B + C)

(ix)

A+(BC)=(AC)+B

Solution
L.H.S = A + ( B C ) =
Mudassar Nazar Notes

+
Page 8

= R.H.S = ( A C ) + B = +

= Hence, A+(B C)=(A C)+B

(x)

2A + 2B = 2 ( A + B )

Solution L.H.S = 2A + 2B

Mudassar Nazar Notes

Page 9

=2

+2

= R.H.S = 2 ( A + B ) =2

=2

=2

= Hence, 2A + 2B = 2 ( A + B )

Question# 8

If

A=

,B=

, then verify that

Mudassar Nazar Notes

Page 10

(i) Solution

(A + B )t = At + Bt

L.H.S = (A + B )t = = = = R.H.S = At + Bt = = = = Hence, (A + B )t = At + Bt t t

t t

(ii) Solution

(A - B )t = At - Bt

L.H.S = (A - B )t

Mudassar Nazar Notes

Page 11

= = = = R.H.S = At - Bt = = = = Hence, (A - B )t = At - Bt t

t t

(iii) Solution

A + At is symmetric

A At

= = +

A + At =

Mudassar Nazar Notes

Page 12

= = (A + At)t (A + At)t Hence, A + At is symmetric = = (A + At)

(iv) Solution

A - At is skew-symmetric

A At

= = -

A At = = = (A At)t = =(A At)t


Mudassar Nazar Notes

= - ( A At)
Page 13

Hence, A - At is skew-symmetric (v) Solution B +Bt is symmetric

B Bt

= = +

B + Bt = = = (B + Bt)t (B + Bt)t Hence, = = (B+ Bt)

B + Bt is symmetric

(vi) Solution

B - Bt is skew-symmetric

B Bt

= = Page 14

B Bt =
Mudassar Nazar Notes

= = (B Bt)t = =(B Bt)t Hence, B - Bt is skew-symmetric = - ( B Bt)

Mudassar Nazar Notes

Page 15

Question # 5

Let A =

,B=

and C =

verify whether

(i) Solution

AB

BA

L.H.S = AB = = = R.H.S = BA = = = Hence, AB BA

Mudassar Nazar Notes

Page 16

(ii) Solution

A(BC) = (AB)C

L.H.S = = = = = R.H.S = (AB)C = = = = = Hence, A(BC) = (AB)C

Mudassar Nazar Notes

Page 17

(iii) Solution L.H.S

A(B+C) =AB + AC

= A(B+C) = = = = = R.H.S = AB + AC = = = = = Hence, A( B+C) = AB + AC +

Mudassar Nazar Notes

Page 18

(iv)

A(B-C) = (A-B)C

Solution L.H.S = A(B-C) = = = = = L.H.S = AB AC = = = = = Hence, A(B-C) = AB AC -

Mudassar Nazar Notes

Page 19

Exercise 1.5 If A = (i) (i) ,B= (AB)-1 = B-1 A-1 ,D=

Question # (6) , then verify that (ii) (DA)-1 = A-1 D-1

Solution AB =

= = 0 (-48) = 0 + 48 = 48 Adj (AB) = L.H.S = (AB)-1 =

. Adj (AB)

Mudassar Nazar Notes

Page 20

= = 4- (-2) =4+2 =6 Adj B = B-1 = B-1 = = Adj A = A-1 =

Adj B

Adj A

R.H.S

= B-1 A-1
= =

Mudassar Nazar Notes

Page 21

=
=

= Hence (AB)-1 = B-1 A-1

(ii)

(DA)-1 = A-1 D-1 Solution DA =

= = 44 (-20) = 44 + 20
Mudassar Nazar Notes Page 22

= 64 Adj (DA) = L.H.S = (DA)-1 =

. Adj (DA)

=
=

= = 8- 0 =8 Adj A = A-1 = A-1 = = = 6-(-2)


Mudassar Nazar Notes Page 23

Adj A

=6+2 =8 Adj D = D-1 =

Adj D

= R.H.S = A-1 D-1


= = =

=
=

= Hence (DA)-1 = A-1 D-1

Mudassar Nazar Notes

Page 24

Review Exercise 1: Question # 7 If A = (i) (i) ,B= (AB)t = Bt At , then verify that (ii) (AB)-1 = B-1 A-1 Solution L.H.S = (AB)t =
=
t

t
t

= = R.H.S = Bt At = =
=

= Hence (AB)t = Bt At

(ii)

(AB)-1 = B-1 A-1


Page 25

Mudassar Nazar Notes

Solution AB =
=

AB = = = 0-10 = -10 = -10 Adj (AB) =


L.H.S = (AB)
-1

Adj (AB)

=
= = -10 (-12) = -10 + 12 =2 Adj B =

Mudassar Nazar Notes

Page 26

Adj B

=
= = -3 2 = -5 = -5 Adj A = =

Adj A

=
R.H.S = B-1 A-1 = = =

=
Hence (AB)-1 = B-1 A-1

Mudassar Nazar Notes

Page 27